KARAKTERISTIK STATUS OBSTETRI PADA PASIEN MIOMA UTERI DI RSUD DR. M. HAULUSSY AMBON TAHUN 2018-2021 - Camelia Gracia Pattinasarany; Novy Riyanti; Halidah Rahawarin; Arlen Resnawaldi; Juliet Sinanu; Merlin M. Maelissa (Fakultas Kedokteran Universitas Pattimura, 2023)
Uterine myoma or uterine leiomyoma or fibroid are benign tumors of the smooth muscle of the uterus, which occur in 20-25% of women of reproductive age. One of the things that can stimulate the occurrence of uterine myoma is estrogen, that is why uterine myoma cannot be identified before puberty and it could shrink or even disappear when entering menopause. Not all uterine myoma have symptoms, the symptoms will appear according to the location where the uterine myoma is sited. Complications can occur depending on the location, which can interfere with the pregnancy until postpartum. This study aims to determine the characteristics of obstetric status in uterine myoma patients at RSUD Dr. M. Haulussy Ambon in 2018-2021. This research is a quantitative descriptive study using secondary data medical records. Sampling in the study is total sampling. Based on the results of the study, in 119 samples, most cases of uterine myoma were found at the age of 36-45 years (44.5%), a secondary education level (51.3%), housewife (66.4%), multipara (47, 1%), and those who have never had an abortion (95.8%). While at least 17-25 years old (1.7%), primary education level (16.0%), retired (0,8%) and Polri/TNI (0.8%), grandemultipara (5.9%), and women who had abortions ≥ 2 times (1.7%).